2003
DOI: 10.1161/01.cir.0000087594.42881.3c
|View full text |Cite
|
Sign up to set email alerts
|

Novel Passive Implantable Atrial Defibrillator Using Transcutaneous Radiofrequency Energy Transmission Successfully Cardioverts Atrial Fibrillation

Abstract: Background-Conventional methods for cardioversion of atrial fibrillation (AF) to sinus rhythm have numerous difficulties. A novel method for cardioversion using the passive implantable atrial defibrillator (PIAD) was tested in acute animal models. This device does not have a battery or a capacitor to store energy and is activated by transferring RF energy across the skin from an external transmitter to the subcutaneously implanted defibrillator. On activation, a novel monophasic shock waveform with 5% tilt is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The role of implantable devices is still under investigation. Hybrid devices that maintain sinus rhythm by multisite atrial pacing and facilitate recurrent internal direct current cardioversion by the delivery of radiofrequency energy 20 have potential for some patients with AF.…”
Section: Future Developments In Direct Current Cardioversionmentioning
confidence: 99%
“…The role of implantable devices is still under investigation. Hybrid devices that maintain sinus rhythm by multisite atrial pacing and facilitate recurrent internal direct current cardioversion by the delivery of radiofrequency energy 20 have potential for some patients with AF.…”
Section: Future Developments In Direct Current Cardioversionmentioning
confidence: 99%
“…Various waveform parameters have been studied in order to increase success. We have previously shown that low-tilt monophasic 3,4 and biphasic 5 waveforms are more successful than conventional higher tilt capacitorbased waveforms for the cardioversion of AF in the laboratory. The aim of this pilot study was to investigate if the low-tilt biphasic waveform was more successful and could be delivered safely in patients with persistent and induced AF.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Ventritex HVSO2 defibrillator (160 F; Ventritex) generated the 3 biphasic waveforms (6 ms in each phase; Figure 1a). A custom-made capacitor-resistance device added to the output circuit enabled waveform rounding.…”
Section: Equipmentmentioning
confidence: 99%
“…U sing an external radio-frequency energy transmitter to transfer energy transcutaneously to the passive implantable atrial defibrillator (PIAD), we recently reported transvenous atrial defibrillation success of 100% at 100 V (1.54Ϯ0.02 J) and pulse width of 10 ms. 1 The PIAD (without a capacitor or a battery), delivering a novel monophasic waveform (slow rising and falling times, a negligible tilt, and rounded leading and trailing edges; Figure 1a), was more efficacious than the standard or rounded monophasic waveforms. 1 Nevertheless, compared with standard monophasic waveforms, biphasic waveforms have improved efficacy in atrial fibrillation (AF) cardioversion, with a reduction in defibrillation threshold.…”
mentioning
confidence: 98%
See 1 more Smart Citation